Prevalence of Epstein-Barr Virus in Some Women Suspected with Breast Cancer in Kaduna State, Nigeria - Kolo R. L.; Suleiman A. B.; Whong C. M. Z.; Elijah Ekah Ella (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Epstein - Barr virus has been associated with several types of epithelial carcinomas; it promotes the oncogenic action of cultivated breast cancer cells through stimulation of HER2 signaling cascades. This work was aimed at determining the seroprevalence of EBV and some risk factors associated with the infection in some women suspected with breast cancer attending Ahmadu Bello University Teaching Hospital, Kaduna state, Nigeria. Serological screening for EBV antibodies was done using Enzyme Linked ImmunoSorbent Assay (ELISA) IgM. Of the one hundred and seventy eight patient samples, one hundred and seven patients were positive for EBV (60.1%). Highest prevalence of 71.7% was recorded in women in the age group 40-49 years old, 70.5% in women with secondary education. Married women in monogamous marriages had highest prevalence of 65.6% and 69.8% respectively. Highest prevalence of 67.2% was recorded in women who had children; women with 1-5 numbers of children also had highest prevalence of 74%. There was a significant association of EBV IgM seroprevalence (p<0.05) with marital status, having children and also number of children the women had. EBV is believed to be a leading contributor to Hodgkin lymphoma, and significant associations have been found between the frequency of Hodgkin lymphoma and breast cancer, which suggests that EBV may also promote some breast cancers.